Feeding artery characteristics and enhancement patterns of hepatoblastoma patients treated with transarterial chemoembolization (TACE): Digital subtraction angiography evaluation - Yus, Teuku M.; Sarastika, Hartono Y.; Soeprijanto, Bambang (Narra Sains Indonesia, 2023)
Hepatoblastoma is one of the most common primary malignant liver tumors in children. The incidence of hepatoblastoma has been increasing, reaching 1.2 per million children now. The transarterial chemoembolization (TACE) procedure is one of the most practical and effective treatment options besides surgery. Digital subtraction angiography (DSA) is performed as the first step of the TACE procedure. The aim of this study was to provide information about the feeding arteries and enhancement pattern of the hepatoblastoma that was assessed by DSA before the TACE procedure. A retrospective study was conducted among hepatoblastoma cases that had undergone DSA on the TACE procedure to obtain information on the vascularity of the tumor. A total of 26 hepatoblastoma cases who had DSA examination as a part of their first TACE procedure were included, consisting of 15 boys and 11 girls, aged between 1–15 years. All cases were stage III and IV according to the Pre-Treatment Extent of Tumor (PRETEXT) staging classification. All hepatoblastoma cases had multiple feeding arteries, most of which were branches of the right hepatic artery. The largest diameter of the feeding artery was 1.82 mm, and the smallest was 0.63 mm. Most cases (84.62%) had strong contrast absorption, and spread evenly, either at the edges or in the center of the tumor. DSA is believed to be an accurate procedure to provide a detailed description of the feeding artery; enhancement patterns of hepatoblastoma were influenced by an adequate TACE.